The genome sequence of the Feathered Gothic, Tholera decimalis (Poda, 1761) [version 1; peer review: 2 approved] - Douglas Boyes; Peter W.H. Holland (Wellcome Open Research, 2023)
We present a genome assembly from an individual female Tholera decimalis (the Feathered Gothic; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 1,334.1 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the Z sex chromosome. The mitochondrial genome has also been assembled and is 15.4 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,771 protein coding genes.